Intrahepatic cysts in biliary atresia after successful hepatoportoenterostomy. Issue 3 (March 1984) - Saito, S; Nishina, T; Tsuchida, Y
Abstract : A patient with an unusual association of biliary atresia and two intrahepatic cysts is reported. The infant was treated by a hepatoportoenterostomy at 2 months of age and by subsequent drainage of the cysts at 13 months. These cysts were detected by ultrasound during a febrile illness.